Evidence for Transcriptional Factor Dysregulation in the Dorsal Raphe Nucleus of Patients with Major Depressive Disorder - Kerman, Ilan A.; Bernard, René; Bunney, William; Jones, Edward; Schatzberg, Alan F.; Myers, Richard; Barchas, Jack; Akil, Huda; Watson, Stanley; Thompson, Robert (Frontiers in Neuroscience, 2012)
Extensive evidence implicates dysfunction in serotonin (5-HT) signaling in the etiology of major depressive disorder (MDD). Dorsal raphe nucleus (DR) is a major source of serotonin in the brain, and previous studies have reported within it alterations in 5-HT-related gene expression, protein levels, receptor binding, and morphological organization in mood disorders. In the present study, we utilized in situ hybridization-guided laser capture microdissection to harvest tissue samples from the middle-caudal subregion of the human DR post-mortem from MDD patients and from psychiatrically-normal comparison subjects. Extracted RNA was prepared for gene expression profiling, and subsequent confirmation of select targets with quantitative real-time PCR. Our data indicate expression changes in functional gene families that regulate: 1) cellular stress and energy balance, 2) intracellular signaling and transcriptional regulation, and 3) cell proliferation and connectivity. The greatest changes in expression were observed among transcriptional regulators, including downregulation in the expression of TOB1, EGR1, and NR4A2 and their downstream targets. Previous studies have implicated these gene products in the regulation of functional domains impacted by MDD, including cognitive function, affective regulation, and emotional memory formation. These observations indicate altered function of several transcriptional regulators and their downstream targets, which may lead to the dysregulation of multiple cellular functions that contribute to the pathophysiology of MDD. Future studies will require single cell analyses in the DR to determined potential impact of these changes on its cellular functions and related circuits.